Seropositivity to tick-borne pathogens in nature management workers in the Netherlands - B.J.A. Hoeve-Bakker; G. Çelik; O.E. van den Berg; C.C. van den Wijngaard; A. Hofhuis; J.H.J. Reimerink; S.F.T. Thijsen; K. Kerkhof (Ticks and Tick-Borne Diseases)
The incidence of tick-borne infections other than Lyme borreliosis and tick-borne encephalitis is rising in Europe, including the Netherlands. Nature management workers, being highly exposed to ticks, serve as valuable sentinels for seroprevalence studies on tick-borne pathogens (TBPs). This study assessed nature management workers’ seropositivity to TBPs including Anaplasma phagocytophilum, Babesia divergens, B. microti, Borrelia burgdorferi s.l., Rickettsia conorii and R. typhi in the Netherlands. In addition, the study examined coexposure to multiple TBPs and identified risk factors for B. burgdorferi s.l.- and A. phagocytophilum-seropositivity.The study included 525 nature management workers who donated serum and completed a questionnaire. Sera were analysed for exposure to A. phagocytophilum, B. divergens, B. microti, R. conorii and R. typhi using immunofluorescence assays. For B. burgdorferi s.l. antibody detection, the recommended two-tier testing strategy was used. Risk factor analysis was performed using logistic regression modelling.Seropositivity was 30.9 % for B. burgdorferi s.l.; 16.4 % for A. phagocytophilum; 6.5 % for R. conorii; 2.3 % for R. typhi; 4.2 % for B. divergens; and 0.4 % for B. microti. Almost half (49.3 %) of the participants demonstrated seropositivity for one or more pathogens. Risk factors for B. burgdorferi s.l.-seropositivity included being male, increasing age and tick bite frequency. For A. phagocytophilum-seropositivity, increasing age and working in North Holland province were significant risk factors.This study illustrates the exposure to TBPs in the Netherlands, emphasizing the need for ongoing vigilance and international collaborations to better understand and address the growing threat of TBPs in regions with demonstrated environmental TBP circulation.